CRIMINAL LAW ENFORCEMENT IN ECONOMIC EXPLOITATION OF CHILDREN IN A LEGAL PERSPECTIVE - Fajriani, Fajriani Oktavianur (Law Research Review Quarterly, 2024)
Economic exploitation of children is one form of trafficking in persons where it is unethical to force children to do work without regard for children's rights. One of the contributing factors is that law enforcement is still weak so that perpetrators feel free to carry out acts of exploitation. The research method used is a qualitative approach using a type of sociological juridical research. This research focuses on criminal law enforcement in economic exploitation of minors. This research produced the following findings: First, economic exploitation of children in a legal perspective, namely Law Number 21 of 2007 concerning the Eradication of Trafficking in Persons and Law Number 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection, Second factor causing economic exploitation of children, Third effectiveness of law enforcement in economic exploitation of children, and Fourth, efforts to overcome economic exploitation of children.